High-purity weight-bearing magnesium screw: Translational application in the healing of femoral neck fracture. (April 2020) - Huang, Shibo; Wang, Benjie; Zhang, Xiuzhi; Lu, Faqiang; Wang, Zongpu; Tian, Simiao; Li, Dongyi; Yang, Jiahui; Cao, Fang; Cheng, Liangliang; Gao, Ziqi; Li, Yangde; et al.
Abstract: Magnesium (Mg)-based metals can be used as next-generation fracture internal fixation devices due to their specific properties. We used vascularized bone grafting fixed by degradable pure Mg screws and obtained satisfactory results in the treatment of osteonecrosis of the femoral head. However, the mechanical properties of these screws make them weaker than those made of traditional metals. In particular, one of the main challenges of using screws made of Mg-based metals is their application in fixation at important weight-bearing sites in the human body. Femoral neck fracture is a common clinical injury. In this injury, the large bearing stress at the junction requires a fixation device with extremely high mechanical strength. Surgery and appropriate internal fixation can accelerate the healing of femoral neck fractures. Traditional internal fixation devices have some disadvantages after surgery, including stress shielding effects and the need for secondary surgery to remove screws. On the basis of previous work, we developed high-strength pure Mg screws for femoral neck fractures. In this study, we describe the first use of high-purity Mg to prepare large-size weight-bearing screws for the fixation of femoral neck fractures in goats. We then performed a 48 weeks follow-up study using in vivo transformation experiments. The results show that these biodegradable high-purity Mg weight-bearing screws had sufficient mechanical strength and a degradation rate compatible with bone repair. Furthermore, good bone formation was achieved during the degradation process and reconstruction of the bone tissue and blood supply of the femoral head and femoral neck. This study provides a basis for future research on the clinical transformation of biodegradable high-purity Mg weight-bearing screws.